2018
DOI: 10.15642/jki.2018.8.1.86-110
|View full text |Cite
|
Sign up to set email alerts
|

Dramaturgi Komunikasi Dakwah Para Da’i di Kota Ambon: Pola Pengelolaan Kesan di Panggung Depan

Abstract: This article discusses the pattern of impression management carried out by the da'i on the front stage in an effort to improve the quality of message transformation to mad’u. Through a good impression management, the persua­sion process occurs which allows the conveyed messages to be well received by mad'u with fullly awareness, not by force. Using dramaturgy approach, researchers conducted participatory observation and in-depth interviews towards 15 da'is in Ambon City who were chosen purposively. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This shows that he is loved and respected by his audience. This is in line with research findings by Sulaeman & Sulastri (2018) that preachers in Ambon City perform dramaturgy on the front stage by familiarizing themselves with their congregations. It also corresponds with Rodiah (2007), who reveals that the Midwife Delima manages her impressions by controlling her verbal and nonverbal communication strategy.…”
Section: Appearance In Preachingsupporting
confidence: 91%
See 1 more Smart Citation
“…This shows that he is loved and respected by his audience. This is in line with research findings by Sulaeman & Sulastri (2018) that preachers in Ambon City perform dramaturgy on the front stage by familiarizing themselves with their congregations. It also corresponds with Rodiah (2007), who reveals that the Midwife Delima manages her impressions by controlling her verbal and nonverbal communication strategy.…”
Section: Appearance In Preachingsupporting
confidence: 91%
“…The findings revealed that using a specific language style when preaching is necessary because language is an effective communication tool. Sulaeman & Sulastri (2018), in their research on the dramaturgy of the Preacher, argued that the Preacher plays a role on the front stage. A preacher is a dramaturg on the main stage.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the new title contains elements of novelty and innovation in da'wah studies. (Sulaeman et al, 2018).…”
Section: Dramaturgy Of Ustadh's Abi Azkakia Da'wah In Mobile Legendsmentioning
confidence: 99%
“…According to the Goffman notion, the da'i's self-image in preaching becomes a reference for controlling impressions, including verbal and nonverbal communication signals. Da'i preaching communication abilities can manifest themselves in the social context on a permanent or momentary basis (Sulaeman, Sulastri, & Nurdin, 2018). The appearance of one's self as an identity is deliberately done so that they can accept it when preaching.…”
Section: Da'i Communication Skills In Interacting With Muslim Convertedmentioning
confidence: 99%